Life satisfaction: a sustainable perspective in old age-physical and mental health - ÇALMAZ, Ayşe; YILMAZEL, Gülay (Faculty of Medicine, Universitas Trisakti, 2025)
Life satisfaction is a subjective concept that reflects individuals’ overall evaluation of their life. It is closely associated with the physical and mental health of older adults. The sustainability of life satisfaction among the elderly is important for both individual happiness and societal well-being for public health. This literature study aims to provide a sustainable perspective by examining the factors influencing life satisfaction in old age through both physical and mental dimensions. This study, designed as a literature review, was prepared by scanning studies published in the last five years (2021-2025) in PubMed, Scopus and Science Direct databases. Older adults with high life satisfaction tend to form healthier relationships with their surroundings, access health services more consciously, and interact more actively with society. In this context, addressing life satisfaction in old age from a physical and mental health perspective contributes to achieving sustainable well-being at both the individual and societal levels. The literature demonstrates that life satisfaction in older adults is directly related to their physical and mental health status. The majority of participants reported that the presence of chronic diseases, mobility limitations, and loss of independence in daily activities negatively affected their life satisfaction. In terms of mental health, symptoms of depression, social isolation, and feelings of loneliness emerge as significant determinants of reduced life satisfaction. The review found that protective factors such as regular health check-ups, an active lifestyle, the presence of social support systems, and support for psychological well-being significantly enhance life satisfaction. Additionally, developing a positive attitude towards aging and having meaningful life goals play a vital role in ensuring sustainable life satisfaction. Based on the literature review, developing policies, practices, and supportive services aimed at improving life satisfaction in older adults is of great importance for promoting healthy and active aging.